Experimental investigation of ASR-affected concrete – The influence of uniaxial loading on the evolution of mechanical properties, expansion and damage indices. (10th June 2020) - Kongshaug, Simen Sørgaard; Oseland, Oddbjørn; Kanstad, Terje; Hendriks, Max A.N.; Rodum, Eva; Markeset, Gro
Highlights: Uniaxial sustained stress reduce the volumetric expansion due to ASR. No transfer of expansion to unrestrained directions was observed. Damage due to ASR is most notable from the reduction of modulus of elasticity. Modulus of elasticity decreases with increasing levels of expansion. Abstract: The alkali silica reaction (ASR) in concrete causes internal localized swelling and micro cracking, which result in expansion and correlated deterioration of the concrete material. The stress state of the concrete is known to affect expansion due to ASR, with an anisotropic stress state giving rise to anisotropic expansion. Similarly, the orientation and extent of micro cracking have a directional effect on the concrete mechanical behaviour. This research studied the effect of sustained uniaxial compressive stress on the evolution of the mechanical behaviour of concrete in compression. Concrete cubes of 230 mm side length were uniaxially restrained and stored in accelerated conditions, with cores drilled in two directions for mechanical tests: a cyclic test in compression, i.e. a stiffness damage test (SDT) and a complete stress-strain test. A clear directional dependency of the mechanical characteristics was found. Furthermore, the results indicate that reduction in modulus of elasticity is well correlated with the expansion in the test direction. On the other hand, the damage indices obtained from the SDT merely relate to the expansion, which puts in question the SDT's ability to predict ASR expansion in stressed concrete and therefore in concrete structures.